Dative Au→Al Interactions: Crystallographic Characterization and Computational Analysis. Issue 1 (21st November 2014) - Devillard , Marc; Nicolas, Emmanuel; Ehlers, Andreas W.; Backs, Jana; Mallet‐Ladeira, Sonia; Bouhadir , Ghenwa; Slootweg, J. Chris; Uhl, Werner; Bourissou , Didier
Abstract Hitherto unknown Au→Al interactions have been evidenced upon coordination of the geminal phosphorus–aluminum Lewis pair Mes2PC(CHPh)AltBu2 (Mes=2, 4, 6‐trimethylphenyl). Four different gold(I) complexes featuring alkyl (Me), aryl (Ph, C6F5), and alkynyl (CCPh) co‐ligands have been prepared. X‐ray diffraction analyses show that P→Au→Al bridging coordination induces noticeable bending of the ligand (the PCAl bond angle shrinks by 13°). This new type of transition metal→Lewis acid interaction has been analyzed by DFT calculations.